Alterações em propriedades químicas e físicas de dois solos irrigados com águas com elevados teores de sais. - Lima, André Souza (Universidade Federal Rural do Semi-Árido, 2011)
This work was carried out with the purpose of verifying the effect of increasing water irrigation depths on soil salinity parameters, in two soil and water conditions at Mossoró, RN, Brazil. The trial was conducted in an entirely randomized design, with four replications, using 0.235 x 0.365 m trays, containing 0.00343 m³ of soil. In each soil, an Oxisol (S1) and an Inceptisol (S2), six irrigation depths were applied (L1=500 mm, L2=1000 mm, L3=1500 mm, L4=2000 mm, L5=3000 mm and L6=5000 mm), using water from wells of the same place of soil collection, plus a control treatment, totaling 56 plots. In both soils were determined parameters of Van Genuchten equation (α, m, n, Өr e Өs), moisture at curve inflection point (Өi), tension at field capacity (hcc), S index, total available water (ADT), bulk density, macroporosity, microporosity and permanent wilting point (PMP). Chemical soil determinations were pH, saturation paste electrical conductivity (CEes), saturation paste sodium absorption rate (RASes), contents of Sodium (Na), Potassium (K) and calcium carbonate (CaCO3), besides the sum of calcium and magnesium contents (Ca+Mg). Data were submitted to regression analysis, when coefficients of the models were tested based on the error mean square of variance analysis. The increase on soil salinity caused an increase on bulk density, which influences the other physical parameters. Parameters of Van Genuchten equation received little influence of the increasing irrigation depths. Values of residual moisture, tension at field capacity, microporosity and permanent wilting point presented different trends for each soil. Increase on CEes and RASes indicate that those soils are prone to salinity problems, while pH increase indicate tendency to soil alcalinization. Values of K and CaCO3 showed a decreasing behavior, indicating that application of salt rich water contributed to replace soil K.
Alterations in chemical and physical properties of two soils irrigated subject to increasing water irrigation.
Keywords: Soil salinity; Water quality; Soil degradation.; Salinidade do solo; Qualidade da água; Degradação do solo.; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM